THE EFFECT OF ECONOMIC GROWTH AND INEQUALITY ON POVERTY IN LAMPUNG PROVINCE IN 2015-2023 - Syifa Asriyani Fauzia; Marselina; Dedy Yuliawan (ZILLZELL MEDIA PRIMA, 2025)
This study aims to examine the impact of economic development and inequality on poverty in Lampung Province in 2015-2023. The data used was in the form of panel data from 15 districts/cities in Lampung Province which was analyzed through a random effect model (REM). This analysis shows that GDP per capita and average years of education have a negative and substantial influence on poverty, but the Gini index has a positive and significant impact. The data shows that economic development and higher education contribute significantly to poverty alleviation, but income inequality exacerbates it. These findings are in line with the theory of economic growth, the downward trickle effect, and the theory of structural poverty and human resources, which underscore the importance of equitable distribution of development results and improving the quality of human resources as a method of poverty alleviation.